A half century of didactic design in mathematics education: A bibliometric analysis - Fardian, Dilham; Suryadi, Didi; Prabawanto, Sufyani; Putri, Amelia Defrianti; Qamariah, Nur (Universitas Maritim Raja Ali Haji, 2024)
This study aims to examine the results of studies on didactic design in mathematics education as a contribution to the advancement of study concerning didactical design research. 1413 research articles on didactic design in mathematics education indexed in Scopus over the past 50 years, from 1973 to 2024, were collected and analyzed using bibliometric analysis. The results show increased studies related to didactic design in mathematics education. Based on the bibliometric analysis using VOSviewer and RStudio, there was a significant increase in publication between 2016 and 2022 but a decrease in 2023. The most frequently appearing keywords in the VOSviewer and RStudio search are “mathematics education,